Stock split rule changes and stock liquidity: Evidence from Bursa Malaysia - S. Amir Tabibian; Zhaoyong Zhang; Abdollah Ah Mand (Journal of Risk and Financial Management, 2021)
We test the impact of stock split rule changes on liquidity behavior in Bursa Malaysia during 2004-2020. Using event study methodology, this study examines stock liquidity on and around stock split days through three subperiods of study, including the first (2004-2006), second (2007-2009), and third (2010-2020) period. We find that liquidity improvement is short-lived in the first and second periods, while it is a long-lived phenomenon in the third period. Firms in the first and second period experienced liquidity improvement only on the split announcement day, while it lasts up to a year after the Ex-date for firms in the third period. Our findings also show a liquidity improvement after the Ex-date only in the third period for the groups of firms categorized based on the liquidity, split factor, and other simultaneous announcements. The findings suggest a positive effect of stock split rule changes implemented by the Securities Commission.
Keywords: 330; Bursa Malaysia; securities regulation; stock liquidity; stock split